Implementasi Pembelajaran Mendalam (Depp Learning) Di Sekolah Dasar Sebagai Penguatan Kurikulum Merdeka - Mujtahid; Hasan Assidiqi, Ali; Sadiyah, Dini (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2025)
This study aims to theoretically examine the implementation of deep learning in elementary schools as a strategy to strengthen the implementation of the Independent Curriculum. The method used in this study is library research, analyzing various scientific sources such as books, educational journals, policy articles, and official documents from the Ministry of Education, Culture, Research, and Technology. Deep learning is understood as an approach that emphasizes in-depth conceptual understanding, critical and reflective thinking skills, and the ability to connect concepts to real-life contexts. The results of the study indicate that the principles of deep learning are highly relevant to the Independent Curriculum approach, particularly in differentiated learning, project-based learning, and formative assessment. This approach not only encourages students to actively construct knowledge but also supports the formation of a Pancasila learner profile. Furthermore, deep learning also has theoretical implications for developing the role of teachers as facilitators, contextualizing learning design, and creating a more meaningful and holistic assessment system. Therefore, it is not surprising that the government will implement deep learning in elementary schools starting in the 2025/2026 academic year. This study recommends conducting further field-based research to directly observe the implementation of deep learning in elementary schools, including the challenges and opportunities in supporting the Independent Curriculum. Therefore, this study is expected to provide theoretical and practical contributions to the field of elementary education in Indonesia as it prepares for a more adaptive and transformative education in the global era.